KARAKTERISTIK KIMIA PUPUK ORGANIK CAIR KEONG MAS DENGAN DUA DEKOMPOSER DAN KOMPOSISI BAHAN BERBEDA - Nurul Istiqomah; Mahdiannoor Mahdiannoor; Siti Zaliha (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The golden snail is a pest of rice plantations; utilized as a base liquid organic fertilizer, mainly the meat part, because it contains much protein, while the shell is left behind. Decomposers are generally added as fungi or bacteria to speed the decompositions. the aim of the research is to know the effect of interaction and single, the best interaction, the type of decomposer, and the best material composition on the chemical characteristic of golden snail liquid organic fertilizer. The testing of nutrients was carried out in the PPLH ULM Laboratory, Banjarbaru, Kalimantan Selatan Province, in July 2020. The research utilized is a Completely Randomized Design with two factors. The first factor is the type decomposer (D), which consists of 2 levels, that are d1 = Trichoderma sp. and d2 = EM4. The second-factor material composition (K) consists of 3 levels, that are k1 = shell, k2 = meat, and k3 = gold snail shell and meat. The result showed an interaction effect on the element Fe variable, with the best treatment having a significant impact on the Mn element variable, and a great influence on N and P elements, with the best treatment being k2.